The secret recipe of Ella Dove - Hawkins, Karen (Hawkins, Karen. Dove Pond series, 2023)
"Three lives converge as a wildly talented baker returns to Dove Pond to face her past in this entry in the charming series that proves that sometimes miracles really do happen. Ella Dove is an acclaimed baker whose desserts spark vivid, cherished memories in those who taste them. A restless soul, Ella goes wherever the wind takes her--but driven by a haunting dream, she's coming home to Dove Pond for an extended visit. Ella believes the dream is a sign it's time she confront and reconcile with her mentor, Angela Stewart Harrington. Years ago, Angela falsely accused Ella of stealing her coveted family recipe book, known as the Book of Cakes. Angela has her own share of amends to make. Her daughter Jules has never forgiven her for divorcing her father, and they've been estranged ever since. But just as Angela begins to hope that she and Jules might mend their tattered relationship, a miscommunication turns into a lie that could destroy everything. Meanwhile, Jules's son Gray is shocked that Ella, his first love and his first heartbreak, has returned to Dove Pond. But even though he knows Ella is a wanderer and will soon leave, he's unable to stop himself from falling for her once again. Can Gray find a way to convince Ella to give him, and their town, a serious chance? Or is he once again on the road to a broken heart? With so much at stake, Ella, Angela, and Gray must learn to accept each other--flaws and all--forgive the many mistakes of their pasts, and trust that love can, and will, always find a way. For fans of Alice Hoffman and Sarah Addison Allen, The Secret Recipe of Ella Dove is a delicious and magical read that will warm your heart and charm your senses."--